Aspergillus and Fusarium corneal infections are regulated by Th17 cells and IL-17 producing neutrophils - Taylor, Patricia R. (2014)
Fusarium and Aspergillus species of mould are major causes of corneal infections in the USA and worldwide, resulting in severe visual impairment and blindness. As there is evidence for T cell responses to these pathogenic fungi in infected individuals, we examined the role of IL-17A (IL-17) and IFN-γ in murine models of fungal keratitis. We found that C57BL/6 mice given intratracheal or subcutaneous immunization of conidia prior to corneal infection exhibited enhanced fungal killing and lower corneal opacity compared with unimmunized mice. Protective immunity was associated with temporal recruitment of IL-17 producing neutrophils, Th17 and Th1 cells, and was dependent on production of IL-17 but not IFN-γ. Protection was also impaired in neutrophil depleted and in Rag2(−/−) mice. Together, the results of these studies identify an essential role for IL-17 producing neutrophils and Th17 cells in regulating the growth of fungal hyphae and the severity of corneal disease.